Kesantunan dalam Tindak Tutur Melalui Kotowaza: Kajian Pragmatik - Hakimi, Iffatu Masrura Al (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 6 No 2 (2024)DO - 10.24843/JS.2024.v06.i02.p04, 2024)
This research focuses on politeness in speech acts through kotowaza (Japanese proverbs). The principle of politeness is needed for daily activities, especially in interacting with other people. Kotowaza is a tool used to convey sarcasm, warnings, warnings, notifications, advice, and even parables consisting of a series of beautiful words. Kotowaza is conveyed implicitly. This study used a descriptive qualitative method. Researchers limit kotowaza to animal elements in Doraemon no Kotowaza Jiten. The data collection technique was carried out using note-taking techniques. Meanwhile, the analysis was carried out using pragmatic studies by observing the principles of politeness according to Leech. Based on the results of the analysis, there are 15 dialogues with animal element kotowaza speech acts in Doraemon no Kotowaza Jiten. In this data, 10 dialogues have polite speech acts and 5 dialogues violate politeness principles. Politeness is important in communication. Therefore, it is necessary to pay attention to the use of maxims in the context of speech acts.